Snapshot of the School Year Algebra 2 Honors Class Alex Asemota Mrs. Vittese Period 4 May 3, 2012.

Slides:



Advertisements
Similar presentations
Start with your equation Move the # term to the other side, and leave a space Determine what HALF of the coefficient of X is Factor the left side Write.
Advertisements

MTH 065 Elementary Algebra II
( ) EXAMPLE 3 Solve ax2 + bx + c = 0 when a = 1
SOLVING INEQUALITIES Final Answer Step 1: Subtract 5 from both sides
Solving 2 Step Equations
Solving Linear Equations Rule 7 ‑ 1: We can perform any mathematical operation on one side of an equation, provided we perform the same operation on the.
Algebraic Fractions and Rational Equations. In this discussion, we will look at examples of simplifying Algebraic Fractions using the 4 rules of fractions.
Solve an equation with variables on both sides
Solve an absolute value equation EXAMPLE 2 SOLUTION Rewrite the absolute value equation as two equations. Then solve each equation separately. x – 3 =
Solve an equation using subtraction EXAMPLE 1 Solve x + 7 = 4. x + 7 = 4x + 7 = 4 Write original equation. x + 7 – 7 = 4 – 7 Use subtraction property of.
© 2007 by S - Squared, Inc. All Rights Reserved.
Holt McDougal Algebra Completing the Square Solve quadratic equations by completing the square. Write quadratic equations in vertex form. Objectives.
EXAMPLE 2 Rationalize denominators of fractions Simplify
1.4 Solving Equations ●A variable is a letter which represents an unknown number. Any letter can be used as a variable. ●An algebraic expression contains.
The Multiplication Principle of Equality 2.3a 1.Solve linear equations using the multiplication principle. 2.Solve linear equations using both the addition.
Multiply polynomials vertically and horizontally
Algebraic long division Divide 2x³ + 3x² - x + 1 by x + 2 x + 2 is the divisor The quotient will be here. 2x³ + 3x² - x + 1 is the dividend.
Warm Up. Algebra 3 Chapter 7: Powers, Roots, and Radicals Lesson 3: Power Functions and Function Operations.
Complete Solutions to Practice Test What are the solutions to the quadratic equation  A. 3, 6  B. 6, 6  C. 3, 12  D. 4, 9  E. -4, -9 Factor.
Solve an equation by combining like terms EXAMPLE 1 8x – 3x – 10 = 20 Write original equation. 5x – 10 = 20 Combine like terms. 5x – =
Solve an absolute value equation EXAMPLE 2 SOLUTION Rewrite the absolute value equation as two equations. Then solve each equation separately. x – 3 =
Copyright © 2014, 2010, 2007 Pearson Education, Inc. 1 1 Chapter 9 Quadratic Equations and Functions.
Example 1A Solve the equation. Check your answer. (x – 7)(x + 2) = 0
Solve an equation using addition EXAMPLE 2 Solve x – 12 = 3. Horizontal format Vertical format x– 12 = 3 Write original equation. x – 12 = 3 Add 12 to.
Example 1 Solving Two-Step Equations SOLUTION a. 12x2x + 5 = Write original equation. 112x2x + – = 15 – Subtract 1 from each side. (Subtraction property.
1.3 Quadratic Equations College Algebra: Equations and Inequalities.
Use the substitution method
PERFECT SQUARE TRINOMIALS
© 2007 by S - Squared, Inc. All Rights Reserved.
Solving One Step Equations with Decimals Example 1 x = x = 3.7 Check: x = 8.6 Does = 8.6? 8.6 = 8.6 Subtract.
Algebra 2 Solving Radical Equations Section 7-5 Solving Square Root and Other Radical Equations Lesson 7-5.
§ 2.2 The Multiplication Property of Equality. Blitzer, Introductory Algebra, 5e – Slide #2 Section 2.2 Properties of Equality PropertyDefinition Addition.
1.2 Quadratic Equations. Quadratic Equation A quadratic equation is an equation equivalent to one of the form ax² + bx + c = 0 where a, b, and c are real.
Substitution Method: Solve the linear system. Y = 3x + 2 Equation 1 x + 2y=11 Equation 2.
1.4 Solving Equations.
Solutions to Special Practice
Solving Absolute-Value Equations
Homework Questions?.
EXAMPLE 2 Rationalize denominators of fractions Simplify
Solving Multi-Step Equations
Solve a literal equation
3-1 HW:Pg #4-28eoe, 30-48e, 55, 61,
Solve a quadratic equation
SOLVING EQUATIONS, INEQUALITIES, AND ALGEBRAIC PROPORTIONS
Solve for variable 3x = 6 7x = -21
Solve an equation by multiplying by a reciprocal
Solve a quadratic equation
Factoring Special Cases
Example 2 4 m 8 m 5m 12 m x y.
Solving One-Step Equations
Solving Multi-Step Equations
Solving Multi-Step Equations
Solve an equation by combining like terms
Equations Containing Decimals
Section 9.2 Using the Square Root Property and Completing the Square to Find Solutions.
You can find the roots of some quadratic equations by factoring and applying the Zero Product Property. Functions have zeros or x-intercepts. Equations.
Solving Multi-Step Equations
Solving one- and two-step equations
Solving Systems of Equations
What is synthetic division?
Solving Multi-Step Equations
Solving Absolute-Value Equations
Solving Multi-Step Equations
Learning Objective Students will be able to: Solve equations in one variable that contain absolute-value expressions.
What is synthetic division?
Solving Equations.
What is synthetic division?
The student will be able to:
Section P4.
Presentation transcript:

Snapshot of the School Year Algebra 2 Honors Class Alex Asemota Mrs. Vittese Period 4 May 3, 2012

Chapter 2  To solve this problem: 2x-3 11  Solve the first inequality:  2x-3<5 (Add 3 on both sides)  2x<8 (Now divide by 2 on both sides)  x<4  Then solve the second inequality:  x+14>11 (Subtract 14 from both sides  x>-3  The solution is:  x>-3 and x<4  This means that all numbers between -3 and 4 are solutions.

Chapter 3  Find function composition given f(x) = 3x and g(x) = x + 2.  Question: f(g(8))  Step 1: Plug in given for x and solve.  g(8) = (8) + 2 = 10  Step 2 : Plug in g(4) for into f function and solve.  f(g(8)) = f(10) = 3(10) = 30

Chapter 4  Solve 4x + 3y = 19 and 5x + 7y = 40  Step 1: Multiply equations to make the coefficients of the x terms additive inverses.  5 (4x + 3y) = 5 19  −4 (5x + 7y) = −4 40  Step 2: Simplify,  20x + 15y = 95  −20x − 28y = −160  Step 3: Then you have to divide to get y  −13y = −65  y = 5  Step 4: Substitute for y in the first equation to get x  4x + 3(5) = 19  4x = 4  x = 1  The solution is (1, 5).

Chapter 5  Solve: x 2 + 5x + 7x + 35  Step 1: Put related terms next to each other  x(x + 5) + 7(x + 5) =  Step 2: Simplify  (x + 7)(x + 5)

Chapter 6  Solve: x + 9/x = 10  x(x + 9/x)=10  Step 1:Multiply through by x to clear the fractions.  x = 10x  Step 2: Subtract 10x to make it all equal 0.  x 2 − 10x + 9 = 0  Step 3: Factor  (x − 1)(x − 9) = 0  Step 4: Solve for 0  x = 1 OR x = 9  Step 5: Check answer  Both 1 and 9 check in the original equation. The solutions are 1 and 9.

Chapter 7  Solve:´√ 3x+3 + √ x+2 = 5  Step 1: Subtract √ x+2: √ 3x+3=- 5 − √ x+2  ( √ 3x+3) 2 = (5 − √ x+2) 2  Step 2: Square the terms,  3x + 3 = 25 − √ x+2 + x + 2  Step 3: Simplify  10 √ x+2 = 24 − 2x  Step 4: Factor and Divide  5 √ x+2 = (12 − x)  Step 5: Square to to cancel square roots  (5 √ x+2) 2 = (12 − x) 2  Step 6-9: Simplify and Solve  25(x + 2) = 144 − 24x + x2  25x + 50 = 144 − 24x + x2  0 = 94 − 49x + x2  0 = (x − 2)(x − 47)  x = 2 OR x = 47  Step 10: Check  2 checks in the original equation; 47 does not check. The solution is 2.

Chapter 8  Solve: 5x2 + 6x + 1 = 0  Step 1 : Plug information for as in ax 2 + bx + c=0  Step 2: Simplify Answer: x = {-1/5, -1}

Chapter 9  Step 1: Start with the given equation  Step 2: Subtract from both sides  Step 3:Factor out the leading coefficient  Step 4: Take half of the x coefficient  Step 5:Now square  Step 6: Now add and subtract this value inside the parenthesis. Doing both the addition and subtraction of does not change the equation  Step 7: Distribute  Step 8: Multiply  Step 9: Now add to both sides to isolate y  Step 10: Combine like terms  Vertex (-1,6)  AoS x= -1  Minimum is the vertex (-1,6)

Chapter 11  Using the Remainder Theorem, find the value of f (–5), for f (x) = 3x4 + 2x3 + 4x.  I need to do the synthetic division, remembering to put zeroes in for the powers of x that are not included in the polynomial:  Since the remainder is 1605, then, thanks to the Remainder Theorem, I know that:  f (–5) = 1605.